Towards biogas production from vinasse and pentose liquor from sugarcane biorefineries - Diego Rafael Mágero Elihimas; Graciano Fernandes de Mendonça; Cláudia Jéssica da Silva Cavalcanti; Mauro Antonio da Silva Sa Ravagnani; Caliane Bastos Borba Costa; Diogo Ardaillon Simões; Sávia Gavazza; Bruna Soares Fernandes (Energy Conversion and Management: X)
Vinasse and pentose liquor are liquid streams produced as waste in sugarcane mills. Biogas production from these streams offers significant potential for energy recovery, contributing to sustainability and reducing fossil fuel dependency. While methane production from vinasse has been extensively studied, the co-digestion of vinasse and pentose liquor for biogas production remains underexplored. This review evaluates the potential of co-digesting these byproducts, by analyzing substrate composition, reactor configurations, and process conditions to optimize methane yield. Key influencing factors include sulfate concentration, temperature, toxic compounds, organic loading rate, and reactor design, which influence microbial activity and the balance between sulfate-reducing bacteria and methanogens. The pretreatment to obtain pentose liquor is especially important for biogas production. Hydrothermal pretreatment is particularly effective, enhancing sugar recovery and minimizing inhibitory compounds like furans, which hinder anaerobic digestion. The results show that vinasse and pentose liquor co-digestion significantly enhance methane production, presenting a promising strategy for maximizing energy recovery. Studies reported an increase in the biochemical methane potential by up to 118%. Additionally, separating the acidogenic and methanogenic phases improves process stability. These findings highlight the potential of these solutions to contribute to the sugarcane industry.